Multiple sclerosis in a 4-year-old boy: a case report and literature review - Arkar, Ula; Vipotnik Vesnaver, Tina; Osredkar, Damjan; Perković Benedik, Mirjana; Bizjak, Neli (Frontiers in Neurology, 2024)
Pediatric onset multiple sclerosis (POMS) in the very young is a very rare entity and presents a difficult diagnostic challenge due to overlapping signs and symptoms with other diseases. We present a 4-year-old boy who initially presented with right-sided hemiparesis and demyelinating lesions on MRI. Follow-up MRI examinations 3 and 6 months later revealed new demyelinating lesions. Ten months after initial presentation, he presented with right-sided hemiparesis, central facial nerve palsy on the right side and new demyelinating lesions on MRI. Two clinical events and new MRI lesions on follow-up MRIs confirmed the diagnosis of POMS. He was treated with rituximab and experienced no further relapses or radiological progression during the follow-up period.